Realizing Gender Equity Through Education - Nur, Rezky Juniarsih; Komariah, Siti; Wilodati, Wilodati (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
Gender stereotypes continue to permeate society, limiting individual potential and impeding progress towards true equality. This research investigates the impact of educational attainment on equality in dispelling these entrenched stereotypes, with the aim of understanding whether educational attainment acts as a catalyst for change. Using a quantitative approach, we surveyed 400 people in Bandung, Indonesia, collecting data on educational background, gender, and levels of gender stereotypes. Using descriptive statistics and regression analysis, we explored the relationship between these variables. Our findings show a significant negative correlation between achieving educational equality and holding gender stereotypes. This suggests that individuals who have equal access to education exhibit lower levels of stereotypical thinking, regardless of their gender. Further analysis delved deeper, showing that individuals with higher levels of education, both male and female, had lower scores on the gender stereotyping measure. This indicates that education plays an important role in challenging traditional gender norms and fostering a more egalitarian perspective. However, the study also identified differences in this relationship. Differences in gender stereotypes existed across demographic groups, with women generally showing higher levels compared to men. These differences highlight the need for further investigation into the complex factors that influence individuals' perceptions of gender roles. Overall, this quantitative analysis strengthens the argument that achieving equality in education is a powerful tool to eliminate harmful gender stereotypes. By providing knowledge, critical thinking skills and exposure to diverse perspectives, education empowers individuals to challenge preconceived notions and embrace a more just society. The findings presented here have valuable implications for policymakers, educators, and community stakeholders who want to create a world free from gender stereotypes and limitations.